PENGARUH KOMITMEN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - masmarulan R (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study aims to determine the effect of commitment and work discipline on the performance of the employees of the Public Works and Spatial Planning Office of Jenneponto Regency This study found that there was a positive and significant effect of commitment and work discipline on employee performance at the Public Works and Spatial Planning Office of Jenneponto Regency, with the formulation of the linear equation Y = 3.544+0.356X1+0.590X2. R square of 0.910 which means that employee performance is influenced by commitment and work discipline by 91%. From this research, the researcher concludes that the variables of commitment and work discipline must be considered and improved to produce good productivity or employee performance so that organizational goals can be achieved.